2014
DOI: 10.4240/wjgs.v6.i7.142
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin and ulcerative colitis: A case report and review of the literature

Abstract: This case report describes a case of ulcerative colitis the onset of which occurred after the use of isotretinoin for acne treatment. Our patient, a healthy male young adult, after several months of isotretinoin use, developed gastrointestinal disorders and after thorough medical workup was diagnosed with ulcerative colitis. The literature regarding a possible correlation between isotretinoin use and ulcerative colitis is scarce. Nevertheless, recent epidemiological studies have shed more light on this possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Since the first detailed report of an association of oral isotretinoin therapy with IBD by Brodin (10) in 1986, a total of 12 cases of isotretinoin-related IBD have been reported in the English literature (11)(12)(13). Many studies concerning the relationship between isotretinoin and IBD have been conducted, but there is no concordance between their results (14).…”
Section: Discussionmentioning
confidence: 99%
“…Since the first detailed report of an association of oral isotretinoin therapy with IBD by Brodin (10) in 1986, a total of 12 cases of isotretinoin-related IBD have been reported in the English literature (11)(12)(13). Many studies concerning the relationship between isotretinoin and IBD have been conducted, but there is no concordance between their results (14).…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism of isotretinoin-induced UC is the prevention of epithelial cell growth and the activation of T-cells. Another theory is that the T-cells activated by isotretinoin express the α4β7 and CCR9 receptors, which are crucial to the gastrointestinal system's inflammation process [12]. Retinoids inhibit the chemotaxis of neutrophils and monocyte and alter neutrophil profiles, generating reactive oxygen species [14].…”
Section: Isotretinoin and The Immune Systemmentioning
confidence: 99%
“…Nevertheless, isotretinoin has been controversially associated with the development of IBD [11]. While recent epidemiological studies and a meta-analysis suggest that isotretinoin does not increase the risk of UC, several lawsuits have been filed implying a correlation between isotretinoin and UC [12]. Important clinical questions inconsistently addressed in guidelines include the association of isotretinoin and IBD.…”
Section: Introductionmentioning
confidence: 99%
“…Although the great majority of patients treated with isotretinoin do not experience the development or aggravation of inflammatory bowel disease (IBD) (74-79), an increased risk of IBD in a subgroup of patients cannot be excluded (80)(81)(82)(83)(84). It is noteworthy, that a recent study reported excessive death of intestinal epithelial cells (IEC) in the ileal and colonic epithelium to represent a major pathogenetic feature of IBD (85).…”
Section: Apoptosis and Inflammatory Bowel Diseasementioning
confidence: 99%